A new species of Bithoracochaeta Stein (Diptera: Muscidae) with comments on Mexican species of the genus and their implication as possible biocontrol agents for greenhouses pests - Jaume-Schinkel, Santiago; Ibáñez-Bernal, Sergio (Zootaxa, 2020)
A new species of Bithoracochaeta Stein, 1911 (Diptera, Muscidae), Bithoracochaeta couriae sp. nov., is described and illustrated. In addition, we present comments on all Mexican species of the genus, a brief description of hunting behavior of B. couriae sp. nov. and its possible use as a biological control agent of greenhouses pests.